La cocina colimense. El menú, muestrario de la cultura regional - David Oseguera Parra (Estudios sobre las Culturas Contemporáneas)
The Cooking of Colima constitutes a faithful showcase for regional culture. Suiting its characteristic history and geography, a unique culinaiy art has developed in this Mexican finisterre, and has been put to the service of a table characterized as contrasting, varied, fresh, laid back, refined and down to earth, festive and everyday. In recent decades many traditional dishes have disappeared from the family menu. This stems from the acceleration of modem life, changes in production systems, enviromental deterioration and the new orientations of taste. Nervertheless, the cuhnary tradition of Colima is resisting and is renewing itself.